POLITICAL MOBILIZATION OF CIGARETTE FACTORY WORKERS IN THE 2024 KUDUS REGIONAL ELECTION: PATRON-CLIENT DYNAMICS AND ELECTORAL PRAGMATISM - Rifqi Gozali; Rina Martini (SOSIOEDUKASI, 2026)
Cigarette factory workers in Kudus Regency (predominantly women) occupy a distinctive socio-economic position shaped by enduring stereotypes that frame them as diligent, compliant, and low-cost labor. In the context of regional head elections (Pilkada), this workforce constitutes a sizable and strategically important electoral constituency. Their numerical concentration makes them a highly contested voting bloc, prompting candidate pairs to devise targeted mobilization strategies. This study examines the political mobilization of cigarette factory workers during the 2024 Regional Head Election in Kudus. Mobilization was conducted through the hierarchical network of the Federasi Serikat Pekerja Rokok, Tembakau, Makanan, dan Minuman Serikat Pekerja Seluruh Indonesia (FSP RTMM-SPSI), extending from union leaders to factory-level foremen (mandor) who acted as intermediaries between political elites and rank-and-file workers. Using a descriptive qualitative approach, the research analyzes patron–client relations linking candidate pairs, union officials, and workers, with particular attention to the distribution of material incentives as instruments of electoral consolidation. The findings reveal a prevailing political pragmatism in Kudus that normalizes vote-buying practices, despite their potential to inflate campaign expenditures and reinforce corruption. The study highlights the persistence of clientelistic mobilization within Indonesia’s local democratic framework.